'Obsessions' in children with autism or Asperger syndrome. Content analysis in terms of core domains of cognition - Baron-Cohen, S; Wheelwright, S (British journal of psychiatry, 1999)
We report a survey of the content of obsessions in children with autism spectrum conditions. We use the term 'obsessions' narrowly, to indicate strong, repetitive interests. We predicted that obsessions would not cluster randomly, but rather would occur significantly more often in the domain of 'folk physics' (an interest in how things work), and significantly less often in the domain of 'folk psychology' (an interest in how people work). These predictions were tested relative to a control group of 33 children with Tourette syndrome. To examine the content of autistic obsessions, and to test the theory that these reflect an evolved cognitive style of good folk physics alongside impaired folk psychology. Ninety-two parents returned a questionnaire designed to determine the subject of their child's obsessional interests. The results were analysed in terms of core domains of cognition. Both predictions were confirmed. These results suggest that impaired folk psychology and superior folk physics are part of the cognitive phenotype of autism. A content-free theory of obsessions is inadequate.